The Influence of Additives on the Interfacial Bonding Mechanisms Between Natural Fibre and Biopolymer Composites - Ghaffar, Seyed Hamidreza; Madyan, Omar Abo; Fan, Mizi; Corker, Jorge (Macromolecular research, 2018)
There has not been extensive research into the subjects of the interfacial bonding quality and the interaction mechanisms of biopolymers and natural fibres. Attempts have been made to incorporate natural fibres/fillers (biofibres) into the manufacture of composites in order to increase the functionality and performance of biopolymers synthesised from natural sources/microbial systems. However, the interfacial bonding quality and other substantial technical challenges still need to be addressed if their industrial use is to be realized. The interfacial bonding quality ultimately dictates the mechanical and physical performance of bio-composites. This review paper attempts to collate the state-of-the-art regarding coupling agents/additives and their roles in interaction mechanisms with biofibres and biopolymers. Two potential pathways for narrowing the performance gap between biopolymer-based bio-composites and their petroleum-based counterparts are: i) improving the interfacial bonding quality by the synthesis of a specific coupling agent, and ii) improving the processability of bio-composites by blending two or more biopolymers.